Design and optimization of self-nanoemulsifying formulations for lipophilic drugs. (6th March 2015) - Zhao, Tianjing; Maniglio, Devid; Chen, Jie; Chen, Bin; Motta, Antonella; Migliaresi, Claudio
Abstract: The purpose of the current study was to develop and optimize novel self-nanoemulsifying drug delivery systems (SNEDDS) with a high proportion of essential oil as carriers for lipophilic drugs. Solubility and droplet size as a function of the composition were investigated, and a ternary phase diagram was constructed in order to identify the self-emulsification regions. The optimized SNEDDS formulation consisted of lemon essential oil (oil), Cremophor RH40 (surfactant) and Transcutol HP (co-surfactant) in the ratio 50:30:20 (v/v). Ibuprofen was chosen as the model drug. The droplet size, ζ -potential and stability of the drug-loaded optimized formulations were determined. The stability of SNEDDS was proved after triple freezing/thawing cycles and storage at 4 °C and 25 °C for 3 months. In vitro drug release studies of optimized SNEDDS revealed a significant increase of the drug release and release rate in comparison to the Ibuprofen suspension (80% versus approximately 40% in 2 h). The results indicated that these SNEDDS formulations could be used to improve the bioavailability of lipophilic drugs.